A comparative study of biological activated carbon based treatments on two different types of municipal reverse osmosis concentrates. (February 2020) - Pradhan, Shovana; Fan, Linhua; Roddick, Felicity A.; Shahsavari, Esmaeil; Ball, Andrew S.; Zhang, Xiaolei
Abstract: A study was conducted to understand the impact of reverse osmosis concentrate (ROC) characteristics on the efficacy of biological activated carbon (BAC) based treatments for removing organics and nutrients from two ROC streams (ROCa derived from municipal waste input with high salinity, and ROCb derived from domestic waste plus industrial trade waste with markedly lower salinity). Fluorescence excitation and emission matrix spectra and molecular weight analysis demonstrated that ROCa and ROCb had a significantly different composition of organic compounds due to the petrochemical processing and abattoir waste compounds in ROCb . Although the sequence of coagulation, UV/H2 O2 and BAC gave the highest organic removal from the two ROCs (67% DOC for ROCa and 62% for ROCb), UV/H2 O2 followed by BAC achieved satisfactory removal (>55%) for both ROC types. Sequential treatment involving coagulation gave better phosphorus removal (>90%) than any single treatment (<65%). Total nitrogen (TN) removal was fairly low (<50%) for all the treatment options and the salinity level had insignificant impact on nitrogen removal. Analysis of bacterial communities suggested that higher phosphorus removal and lower total nitrogen and nitrate removal from ROCb than ROCa was related to the presence of various denitrifying or phosphorus accumulating bacteria in the BAC. Graphical abstract: Image 1 Highlights: The effect of different treatment strategies on two ROC streams was investigated. Two ROCs showed different organic compositions affecting the treatment efficacy. Satisfactory organic removal from both ROCs was achieved by UV/H2 O2 -BAC. The salinity of both ROCs had limited impact on organic and nitrogen removal by BAC.